2014
DOI: 10.1128/jb.02070-14
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Formation and Its Regulation in Ruminococcus albus: Involvement of an Electron-Bifurcating [FeFe]-Hydrogenase, of a Non-Electron-Bifurcating [FeFe]-Hydrogenase, and of a Putative Hydrogen-Sensing [FeFe]-Hydrogenase

Abstract: bRuminococcus albus 7 has played a key role in the development of the concept of interspecies hydrogen transfer. The rumen bacterium ferments glucose to 1.3 acetate, 0.7 ethanol, 2 CO 2 , and 2.6 H 2 when growing in batch culture and to 2 acetate, 2 CO 2 , and 4 H 2 when growing in continuous culture in syntrophic association with H 2 -consuming microorganisms that keep the H 2 partial pressure low. The organism uses NAD ؉ and ferredoxin for glucose oxidation to acetyl coenzyme A (acetyl-CoA) and CO 2 , NADH f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
116
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(129 citation statements)
references
References 82 publications
13
116
0
Order By: Relevance
“…1C). A similar organization recently was identified in a study of Ruminococcus albus hydrogenases, where rex, Ra_adhE, and hydS were in a transcriptional unit with a putative ferredoxindependent hydrogenase, and this locus is believed to play an important part in the sensory and regulatory mechanism of electron metabolism in R. albus (44). In C. thermocellum, this gene cluster may play a similar role.…”
Section: Discussionmentioning
confidence: 84%
“…1C). A similar organization recently was identified in a study of Ruminococcus albus hydrogenases, where rex, Ra_adhE, and hydS were in a transcriptional unit with a putative ferredoxindependent hydrogenase, and this locus is believed to play an important part in the sensory and regulatory mechanism of electron metabolism in R. albus (44). In C. thermocellum, this gene cluster may play a similar role.…”
Section: Discussionmentioning
confidence: 84%
“…As with the group 2b and 2c [NiFe]-hydrogenases, the operons encoding these hydrogenases contain predicted PAS domains (Figure 2) that likely transduce the signal of hydrogenase activity to downstream components via a redox-active heme. There is some transcriptional evidence that the putative phosphatase-linked sensory hydrogenases of Thermoanaerobacterium saccharolyticum (Shaw et al, 2009) and Ruminococcus albus (Zheng et al, 2014) regulate the transcription of group A [FeFe]-hydrogenases, but it has yet to be biochemically confirmed that these enzymes have a regulatory role. Other sensory hydrogenases may regulate wider cellular functions (for example, motility) in response to changes of pH 2 in anoxic environments.…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, the discovery of electron bifurcation has expanded our understanding of how energy is conserved in anaerobic processes such as cellulolytic fermentation, acetogenesis and methanogenesis (Schut and Adams, 2009;Kaster et al, 2011;Buckel and Thauer, 2013;Schuchmann and Muller, 2014). Other themes, including H 2 sensing within anaerobes (Zheng et al, 2014) and H 2 fermentation in aerobes , are emerging.…”
Section: Introductionmentioning
confidence: 99%
“…26 There is also growing evidence that H 2 sensing has a role in anaerobic microorganisms. 19,29 This assortment of functions is supported by the great phylogenetic diversity of the hydrogenases. 19 Hydrogenases can be subdivided into 3 distinct classes based on their metal site, the [NiFe], 20 [FeFe], 23 and [FeFe] hydrogenases are highly diverse in their redox centers, associated subunits, and wider cellular integration.…”
Section: Introductionmentioning
confidence: 98%